Exploring Challenges of the Fourth Industrial Revolution - Tan, Seng Teck; Subramaniam, Hemashwary; Sorooshian, Shahryar (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Fourth industrial revolution (IR 4.0) refers to where manufacturing industries absorbed by intelligent equipment such as products and machines which able to generate intelligent systems and networks. This will help to communicate with each other autonomously. Intelligent sensing, wireless sensor networks and CPSs are fundamental technologies which Germany focusing on. IR 4.0 will include effective independent physical systems associated with each other and smart operations will be carried out by the environment. The IR 4.0 as a revolution empowered by application of advanced progresses at era level to bring unused values and organizations for clients and organization itself. Researcher believes that the outcomes of this study may contribute to the manufacturing to understand the challenges of the fourth industrial revolution that may occur and to finds out the solution in order to ensure the success of this emerging industry.